Assessment of infrastructure of first referral unit facilities in Surguja division: a responsibility of providing emergency obstetric care - Ekka, Abha; Gupta, Shubra A.; Sahu, Divya; Minj, Anmol Madhur; Soni, G. P. (International Journal Of Community Medicine And Public Health, 2019)
Background: Availability of emergency obstetric care (EmOC) is one of interventions to reduce maternal and newborn deaths. The health system fails when effective and affordable health interventions do not reach the population, when Poor infrastructure, drugs and equipment are lacking, and qualified human resources are scarce. The objective of the present study was to assess the availability of EmOC infrastructure in first referral units (FRUs) of Surguja division, Chhattisgarh. Methods: A cross sectional study was designated with 13 FRUs of Surguja division. A semi structured, closed-ended questionnaires was observed on the basis of check list, reviewing record, and interview by available staff. Results: FRUs of Surguja division for physical infrastructure scored 68.5%, for essential medicine 69.2%, for equipments 50.7%, for instruments 45.3% and for availability of blood 34.6%, for health man power category of specialist score was 25.7% but for supportive staff 65.4%. Conclusions: Our study revealed three existing bottlenecks in the healthcare delivery system as inadequate civil infrastructure, short fall of specialists as well as inadequate supplies of drugs and equipment, hampering the function of facility.